(untitled) (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
The article is devoted to the main purpose of teaching the plant - to give deep knowledge and moral education to future generations, thanks to which they are brought up in an endless love for life, for their homeland, for their people.